The effect of time management, motivation, and independence on mathematics learning outcomes with a focus on mediation - Hidayati, Siti Nur; Tusyanah, Tusyanah; Ismiyati, Ismiyati; Tasya, Azza Man (Annals of Mathematical Modeling, 2025)
This research aims to determine the role of learning focus in mediating the effect of time management, learning motivation, and learning independence on mathematics learning outcomes. This study used a quantitative method with data collection through questionnaires and analyzed with SEM-PLS. The sampling technique was saturated sampling, where all 105 students of grade IX of Nafsa Zakiyyah Junior High School in the 2025/2026 academic year were respondents. The results showed that of the 10 (ten) hypotheses proposed, 5 (five) hypotheses were accepted and 5 (five) hypotheses were rejected. The results showed that time management had a positive but insignificant effect on mathematics learning outcomes, learning motivation had a positive and significant effect on mathematics learning outcomes, learning independence had a positive and significant effect on mathematics learning outcomes, learning focus had a positive and significant effect on mathematics learning outcomes, time management had a positive but insignificant effect on learning focus, learning motivation had a positive and significant effect on learning focus, learning independence had a positive but insignificant effect on learning focus. Then, time management mediated by learning focus has a positive but insignificant effect on mathematics learning outcomes, learning motivation mediated by learning focus has a positive and significant effect on mathematics learning outcomes, and learning independence mediated by learning focus has a positive but insignificant effect on mathematics learning outcomes.